The Impact of The Level of Education And The Material Condition of The Population on The Unemployment Rate In Romania - Alina CRISMARIU (SOMITCA); Sorin SOMITCA; Elena HLACIUC (Communications of International Proceedings, 2022)
This paper aims to analyze the impact of the level of education and the material condition of the population on the unemployment rate in Romania. In order to achieve the proposed goal, we analyzed time series for the period 2011-2019 for a series of variables related to the educational and material level of the Romanian population, as well as the unemployment rate. The variables considered are the unemployment rate, the population according to the level of education, sex, age and professional status, the rate of material status by age groups, the population at risk of poverty, the employment rate of recent graduates, the rate of early leaving in education and training, the 18-24 age group. By applying econometric processing methods in the Eviews program, we determined a linear regressive model, useful for explaining the links between the unemployment rate and the level of education, respectively the material condition, which allows us to formulate a series of conclusions and recommendations for better integration into labor marke.
Keywords: unemployment; education; poverty rate.